Diseño de un molde de inyección para la producción de la junta de expansión sanitaria de 3 pulgadas en PVC para PAVCO Wavin (2022)
The purpose of this project is to realize the design of an injection mold for the production of the 3-inch PVC sanitary expansion joint for the company PAVCO WAVIN, where it looking the elimination of the current process of machining on the lathe and the manual location of the reference tag. The characterization of the expansion joint and the manufacturing material is essential to understand the injection molding process, as well, what are the variables that control and/or affect directly the process and how it influences in the design of the mold on the obtaining of a good final product. Looking to guarantee the technical specifications recommended by the company.